Dever de cooperação interestatal para prevenir dano ambiental transfronteiriço, aportes da experiência européia para o Mercosul - Bittencourt, João Alexandre Netto (2007)
This dissertation has for design to identify the responsibilities of cooperation in front of environmental pollution, especially in the regional places, in this case, European Union and MERCOSUL. The normative that present this responsibilities are understood as species of more superficial impositions, where can have a larger engagement of the countries parts of the agreements for it execution. It to notice that the effectiveness of the international norms doesn't occur for obligation, since an organ supreme coercive doesn't exist, but for the interest that States give to it, therefore, norms more appropriate, as the cooperation can present a better result. It is noticed that in spite it to be a diverse form of legislation, such responsibilities are inserted in the International Law of the Environment, as well as in the regional places, especially in Mercosul, presenting countless ways that States cooperates for the environmental preservation, since the reflexes of the environmental damages are not stanchings, they are not " privileges " of the country that causes of the harmful conduct, but they are not respect the borders, tehy accompany the global world. A good solution to interpret the cooperation norms is the human rights and the human person's dignity.